Misfits in the world: culture shifting through crip cultural practices: Desajustados no mundo: mudança cultural através de práticas culturais aleijadas - Chandler, Eliza; East, Lisa; Rice, Carla; El Kadi, Rana (Revista Mundaú, 2023)
Drawing on our participation in D/deaf, disability, and mad arts in North America (Turtle Island), this paper introduces and explores how “crip cultural practices,” cultural practices born out of disability culture that centre disabled people and our politics, contribute to micro acts of world-making. We begin with a description of how the early days of the pandemic served as a cultural disruptor that challenged us to think about how we gather in arts and culture. Following this, we offer a brief review of how disability studies and disability activism critiques normalcy. Considering how arts and cultural organizations have responded to COVID-19 public health measures, we argue that the sector has largely failed to seek out “crip wisdom” (Lakshmi Piepzna-Samarasinha, 2016), preventing the transformation of stop-gap pandemic practices into sustainable crip cultural practices. We end with a few key examples that demonstrate how crip cultural practices gesture towards cripped worlds necessary for disabled people’s survival.